Approaches and geographical locations of respectful maternity care research: A scoping review - Hannah L. Shuman; Annika M. Grupp; Lauren A. Robb; Katherine G. Akers; Gurbani Bedi; Miloni A. Shah; Andrea Janis; Caroline G. Caldart; Urvashi Gupta; Janki K. Vaghasia; Aishwarya Panneerselvam; Aisha O. Kazeem; et al. (PLoS ONE, 2023)
Background Peripartum mistreatment of women contributes to maternal mortality across the globe and disproportionately affects vulnerable populations. While traditionally recognized in low/low-middle-income countries, the extent of research on respectful maternity care and the types of mistreatment occurring in high-income countries is not well understood. We conducted a scoping review to 1) map existing respectful maternity care research by location, country income level, and approach, 2) determine if high-income countries have been studied equally when compared to low/low-middle-income countries, and 3) analyze the types of disrespectful care found in high-income countries. Methods A systematic search for published literature up to April 2021 using PubMed/MEDLINE, EMBASE, CINAHL Complete, and the Maternity & Infant Care Database was performed. Studies were included if they were full-length journal articles, published in any language, reporting original data on disrespectful maternal care received from healthcare providers during childbirth. Study location, country income level, types of mistreatment reported, and treatment interventions were extracted. This study was registered on PROSPERO, number CRD42021255337. Results A total of 346 included studies were categorized by research approach, including direct labor observation, surveys, interviews, and focus groups. Interviews and surveys were the most common research approaches utilized (47% and 29% of all articles, respectively). Only 61 (17.6%) of these studies were conducted in high-income countries. The most common forms of mistreatment reported in high-income countries were lack of informed consent, emotional mistreatment, and stigma/discrimination. Conclusions Mapping existing research on respectful maternity care by location and country income level reveals limited research in high-income countries and identifies a need for a more global approach. Furthermore, studies of respectful maternity care in high-income countries identify the occurrence of all forms of mistreatment, clashing with biases that suggest respectful maternity care is only an issue in low-income countries and calling for additional research to identify interventions that embrace an equitable, patient-centric empowerment model of maternity care.